Small trocar site hernia after laparoscopy - Ben-Shian Huang; Kok-Min Seow; Kuan-Hao Tsui; Wen-Hsiang Su; Chien-Hsing Lu; Peng-Hui Wang (Wolters Kluwer Medknow Publications, 2013)
This review article is attempted to review the cases of 5-mm trocar site hernias (TSHs) after laparoscopic surgery and identify the risks associated with incarceration. We searched the English literature on the PubMed website using the key words "trocar site hernia" and "5 mm". We evaluated a total of 24 cases of 5-mm TSHs and analyzed and results showed that 17 (71%) and 7 (29%) resulted from gynecologic and gastrointestinal surgeries, respectively. The majority were found at the lateral abdomen (87.5%) and recognized within 2 weeks (87.5%). The most frequently herniated organ (n = 14) was the small bowel. Up to 62.5% of cases (n = 15) were repaired by exploratory laparotomy, and 25% (n = 6) required resection of herniated organs secondary to incarceration. The cases with incarceration were detected at 4.3 ± 2.2 days post-operation and those without incarceration at 47.4 days post-operation. No risk factors could be identified to show a correlation between 5-mm TSHs and incarceration. We concluded that immediate 1--2-week postoperative care is of most importance, since the majority of 5-mm trocar site hernias with or without incarceration occurred within this period.